2021
DOI: 10.1080/00224499.2021.1907526
|View full text |Cite
|
Sign up to set email alerts
|

Developing Valid and Feasible Measures of Sexual Consent for Experience Sampling Methodology

Abstract: Preliminary evidence indicates that people’s sexual consent (i.e., their willingness to engage in sexual activity and communication of that willingness) varies across time and context. Study designs that assess sexual consent at multiple time points (e.g., experience sampling methodology [ESM]) are needed to better understand the within-person variability of sexual consent. However, extant validated measures of sexual consent are not appropriate for ESM studies, which require shorter assessments due to the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…For example, they might select the item(s) with the largest factor loading(s) (Fisher & To, 2012 ). Thus, another strength of the present study was our use of measures that underwent a rigorous development process to ensure their validity (i.e., face, content, convergent, and divergent) and reliability (Willis, Jozkowski et al, 2021 ). Still, these measures may be limited in that (1) although we asked participants at the beginning of the study to only reference sexual activity with their primary partner, we were unable to determine with certainty whether they only reported sexual behavior with that same person during the study period and (2) even though we provided participants with operational definitions, they had to engage in a degree of meta-cognition to identify their sexual consent communication as explicit or implicit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, they might select the item(s) with the largest factor loading(s) (Fisher & To, 2012 ). Thus, another strength of the present study was our use of measures that underwent a rigorous development process to ensure their validity (i.e., face, content, convergent, and divergent) and reliability (Willis, Jozkowski et al, 2021 ). Still, these measures may be limited in that (1) although we asked participants at the beginning of the study to only reference sexual activity with their primary partner, we were unable to determine with certainty whether they only reported sexual behavior with that same person during the study period and (2) even though we provided participants with operational definitions, they had to engage in a degree of meta-cognition to identify their sexual consent communication as explicit or implicit.…”
Section: Discussionmentioning
confidence: 99%
“…I nonverbally communicated my willingness to engage in these sexual behaviors Nonverbal cues These items were designed to assess five types of internal consent feelings and four types of active consent communication. The operational definitions that were used to develop these items are included in Willis, Jozkowski et al ( 2021 ). Participants were provided the operational definitions for these constructs before participating in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous research has found that sexual arousal can influence sexual consent perceptions (Benbouriche et al, 2019 ). Further, experience sampling methodology could be used to assess in-the-moment consent perceptions as has been done with self-reports of internal consent feelings and external consent communication (Willis et al, 2021b ). By collecting daily data on people’s sexual consent perceptions over time, researchers would be able to investigate the trends in people’s lived sexual consent process and examine the contexts in which people’s perceptions of another person’s willingness might be associated with their own experiences or communication of willingness.…”
Section: Discussionmentioning
confidence: 99%
“…We also included a four-item measure of active sexual consent communication (Willis et al, 2021a). Specifically, these items assessed the extent that participants relied on explicit cues, implicit cues, verbal cues, or nonverbal cues to communicate their willingness to engage in their most recent partnered sexual activity.…”
Section: Methodsmentioning
confidence: 99%